Clinical impact of CREDO-kyoto risk score on in-hospital bleeding in patients with acute coronary syndrome. (14th October 2021) - Minematsu, Y; Natsuaki, M; Yoshioka, G; Shinzato, K; Nishimura, Y; Nishikido, T; Node, K
Abstract: Background/Introduction: CREDO-Kyoto bleeding risk score was developed to predict the post-discharge bleeding events in patients with percutaneous coronary intervention. However, there were limited reports of the effectiveness of this score to predict the in-hospital bleeding events in patients with acute coronary syndrome (ACS). Methods: We evaluated 562 consecutive ACS patients in Saga university hospital between 2014 and 2019. Primary outcome was major bleeding during hospitalization. Major bleeding was defined as the GUSTO moderate/severe bleeding. Patients were classified into three groups according to the CREDO-Kyoto bleeding risk score (low, intermediate and high). Results: Major bleeding events occurred in 12.1% of all patients during hospitalization. Patients in the high risk group (n=22) had significantly higher incidence of major bleeding than those in the intermediate (n=113) and the low risk groups (n=427) (22.7%, 18.6%, versus 9.8%, respectively, p=0.018, see figure). Multivariate analysis showed that intermediate and high risk groups were independent predictors for the in-hospital major bleeding. Conclusions: CREDO-Kyoto risk score successfully identified high risk ACS patients for the major bleeding during hospitalization. FUNDunding Acknowledgement: Type of funding sources: None.